DESIGN OF A WEB-BASED INVENTORY SYSTEM AT PT. TAINAN ENTERPRISES INDONESIA HO - Reza Ahmad Fauzi; Henri Septanto (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
This research was conducted at PT. Tainan Enterprises Indonesia, a large garment industry company located in Kawasan Berikat Nusantara (KBN), North Jakarta, focusing on stock management and recording processes within the inventory system of the Sample Room. Currently, the inventory system used is manual, leading to potential recording errors, discrepancies between physical stock and documentation, and time inefficiencies. To address these issues, this study developed a web-based information system to automate the recording and management of stock items, allowing for more efficient and accurate data storage and easier stock monitoring through informative data visualization. In designing the web application for the inventory system, the authors employed the waterfall method, a software development approach that follows a linear and sequential order. The development process was carried out in stages, starting with requirements analysis, followed by design, implementation, and testing. The research results indicate that this system successfully enhanced employee productivity, operational efficiency, and reduced recording errors. The implementation of the web-based information system provided an effective solution for improving accuracy, efficiency, and ease of inventory monitoring, demonstrating that digitizing inventory processes significantly benefits the company's performance and operations.